Virtual Religious Manipulation And Psychological Vulnerabilities Of Adolescents (Zien Journal of Social Sciences and Humanities, 2026)
This article provides a scientific analysis of the impact of virtual religious manipulation on the psychological state of adolescent individuals. The study highlights psychological vulnerability factors characteristic of adolescence, including emotional instability, identity formation, the need for social approval, and insufficient development of critical thinking skills.In addition, the cognitive and emotional mechanisms of manipulative religious influence carried out through the internet and social media are also analyzed